Monitoring Baby Incubator Central through Internet of Things (IoT) based on Raspberry Pi Zero W with Computer Monitoring) - Fransiska Ima Setia Ningsih; Bambang Guruh Irianto; Lamidi Lamidi; Mohanad Abdulhamid (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Premature infants, with a gestational age of 37 weeks or less and weighing less than 2500 grams, face challenges in adapting to the outside world due to the underdeveloped state of their organ systems. Special care is essential to support their growth and development, including maintaining optimal temperature, humidity, and oxygen levels similar to those experienced in the mother's womb. Baby incubators play a crucial role in providing these conditions. This study aims to develop a convenient monitoring tool for midwives and healthcare workers responsible for multiple baby incubators. The tool operates independently and is compatible with various brands of baby incubators. Leveraging an IoT system, it utilizes ESP32 and Raspberry Pi Zero W modules for data transmission. The tool incorporates a DS18B20 sensor for monitoring skin temperature and a DHT22 sensor for monitoring the temperature inside the incubator chamber. Using a pre-experimental design with an after-only research design, the tool's measurements are compared against an incubator analyzer. The study reveals that the developed module still exhibits some measurement errors. However, despite these limitations, the research is expected to greatly assist medical personnel in simultaneously monitoring multiple baby incubators. Keywords : Premature infants, Baby incubators, IoT, Temperature, ESP32, Raspberry Pi Zero W